A flexible QoS architecture for DVB‐RCS2. (9th May 2013) - Fairhurst, Gorry; Secchi, Raffaello; Yun, Ana; Skinnemoen, Harald
SUMMARY This paper presents a QoS, architecture for the Higher Layers Satellite in the second generation Digital Video Broadcasting with Return Channel via Satellite standard. It describes the flexibility offered by integrating link and network functions to support internet protocol‐based differentiated QoS. The operation of key mechanisms is outlined and analysed to show how these may be combined to realise differentiated services by defining mappings between per‐hop behaviours, to queues in the traffic plane and return channel satellite terminal request classes in the control plane. Simulation is used to show that an appropriate mapping can be used to can tune the offered service to different traffic classes and that an appropriate assignment can significantly improve the satellite bandwidth efficiency and/or the performance/QoS supplied to a traffic class. Copyright © 2013 John Wiley & Sons, Ltd.